- #1

- 193

- 0

## Main Question or Discussion Point

Let say that a+b=c

this can be writtem as

4a-3a+4b-3b=4c-3c

by arranging

4a+4b-4c=3a+3b-3c

taking out the constants

4*(a+b-c)=3*(a+b-c)

So 4=3

The mistake is that .... I'll post it soon. i read this from a notebook of my little brother and i firstly agreed to it but by the time i found out why not! Test your knowledge too.

this can be writtem as

4a-3a+4b-3b=4c-3c

by arranging

4a+4b-4c=3a+3b-3c

taking out the constants

4*(a+b-c)=3*(a+b-c)

So 4=3

The mistake is that .... I'll post it soon. i read this from a notebook of my little brother and i firstly agreed to it but by the time i found out why not! Test your knowledge too.